Prayer and Power: A New Women’s Tradition in a Ukrainian Village - Lesiv, Mariya (Ethnologies, 2012)
A young girl from the western Ukrainian village of Horodnytsia was seriously ill. In 2007, a family in Germany sent her a statuette of the Mother of God that was said to have miraculous power. The gift was intended to help the girl to recover from her illness. The statuette took on a new purpose, developing into a new tradition. It was incorporated into a homemade altar that traveled from house to house, accompanied by many local women performing religious songs and prayers. This paper draws attention to the Horodnytsia ritual’s collective significance. From an emic perspective, as shared by the ritual’s practitioners, the new tradition communicated women’s response to the ongoing post-Soviet socio-economic crisis. From my own, etic, perspective, informed by performance and gender studies, the altar’s role appeared to expand beyond this, revealing women’s creative, though unselfconscious, attempt to subvert the patriarchal order of vernacular Christianity. The ritual empowered the village women, especially because it was shaped by the familiar model of religious authority. The women consecrated their domestic space following a well-known pattern of church spatial organization. They established their own authority through the development of a kind of close contact with the sacred that they could not achieve in the context of the traditional church.